Attenuation of adhesion, quorum sensing and biofilm mediated virulence of carbapenem resistant Escherichia coli by selected natural plant products. (March 2016) - Thakur, Pallavi; Chawla, Raman; Tanwar, Ankit; Chakotiya, Ankita Singh; Narula, Alka; Goel, Rajeev; Arora, Rajesh; Sharma, Rakesh Kumar
Abstract: The multi-drug resistance offered by Carbapenem Resistant Escherichia coli (Family: Enterobacteriaceae; Class: Gammaproteobacteria) against third line antibiotics can be attributed towards its ability to develop biofilm. Such process involves adhesion and quorum-sensing induced colonization leading to biomass development. The present study explored the anti-adhesion, anti-quorum sensing and anti-biofilm potential of 05 pre-standardized potent herbals. Berberis aristata (PTRC-2111-A) exhibited maximum potential in all these activities i.e. 91.3% ± 0.05% (Anti-adhesion), 96.06% ± 0.05% (Anti-Quorum sensing) and 51.3% ± 0.07% (Anti-Biofilm formation) respectively. Camellia sinensis (PTRC-31911-A) showed both anti-adhesion (84.1% ± 0.03%) and anti-quorum sensing (90.0%) potential while Holarrhena antidysenterica (PTRC-8111-A) showed only anti-quorum sensing potential as compared to standards/antibiotics. These findings were in line with the molecular docking analysis of phytoligands against Lux S and Pilin receptors. Furthermore, the pairwise correlation analysis of the tested activities with qualitative, quantitative and bioactivity functional descriptors revealed that an increased content of alkaloid, moderate content of flavonoids and decreased content of tannins supported all the three activities. In addition, nitric oxide and superoxide scavenging activity were found to be correlated with anti-quorum sensing activity. The findings indicated clearly that B. aristata (Family: Berberidaceae) and C. sinensis (Family: Theaceae) were potent herbal leads with significant therapeutic potential which further needs to be explored at pre-clinical level in the future. Graphical abstract: Highlights: Three steps of Biofilm formation were identified as Bacterial adhesion, Quorum sensing and Biofilm biomass formation. Berberis aristata, Camellia sinensis, Holarrhena antidysenterica showed anti-adhesion, anti-quorum sensing and anti-biofilm activity. Molecular docking of phyto-ligands with Lux S and Pilin receptors also validated the findings. An increased content of alkaloid and flavonoids with decreased content of tannins is responsible for biofilm inhibition. Decrease in nitric oxide and superoxide scavenging activities are also directly linked to biofilm inhibition.